Sport and the brain : the science of preparing, enduring and winning. - Wilson, Mark (Mark R.) (Associate professor of experimental psychology & human movement science); Walsh, Vincent, 1961-; Parkin, Beth (Progress in brain research, 2017)
Sport and the Brain: The Science of Preparing, Enduring and Winning, Part B, Volume 233 reflects recent advancements in the understanding of how elite athletes prepare for, and perform at, peak levels under the demands of competition. Topics discussed in this new release include a section on Exploring the Applicability of the Contextual Interference Effect in Sports Practice, The Resonant System: Linking Brain-body-environment in Sport Performance, the Effects of Acute High-intensity Exercise on Cognitive Performance in Trained Individuals: A Systematic Review, Moving Concussion Care to the Next Level: The Emergence and Role of Concussion Clinics in the UK, and Neurocognitive Mechanisms of the Flow State. This longstanding series takes a multidisciplinary approach, focusing on aspects of psychology, neuroscience, skill learning, talent development and physiology. Takes a multidisciplinary approach, focusing on aspects of psychology, neuroscience, skill learning, talent development and physiologyFocuses on sports and the brainContains expertise and an international focus of contributorsAdopts the novel approach of having a target article with critical commentaries on the lessons learned from British multiple gold medalists at Olympic and World Championships